Analysis of the Influence of Inflation, BI Rate and Exchange Rates/Exchange Rates on the Profitability of National Bank in Indonesia in 2017-2021 - Adyanto Armando Purba; Desry Situngkir; Mentari Purba; Hasyim (Indonesian Journal of Advanced Research, 2023)
This study aims to look at the analysis of the effect of inflation, the BI rate, the exchange rate on the profitability of the National Bank in Indonesia in 2017 – 2021. This study took a sample using a purposive sampling method. The data collection technique used in this study was literature study by obtaining data from BPD. Data analysis was performed with multiple linear regression. The analysis shows that inflation has a negative impact on bank profitability. The higher the inflation, the lower the bank's profitability. In addition, the BI rate has a positive impact on bank profitability. The higher the interest rate, the higher the bank's profitability. Finally, the exchange rate does not have a significant impact on bank profitability. While changes in currency exchange rates can affect a bank's performance in the short term, other long-term political factors such as economic growth and stability have a greater impact big on bank profitability.